Optimization tools in management and finance - Ferreira, M. A. M. (2016)
Through this paper, the most commonly used in management and finance optimization problems mathematical tools are presented, in a combined coherent way. The respective mathematical fundaments are synthetically outlined and the resolution methods are briefly described, hopping that this text functions as a manual in these matters.